Serotyping of Adenoviruses Using Immune Electron Microscopy - Vassall, John H. (1974)
Immune electron microscopy may be used to determine the type specificity of several common human adenoviruses. The method described utilized equine antisera and was used to serotype adenoviruses within hours after typical cytopathic effect was observed in tissue culture. Adenovirus types 1, 2, 3, 5, 7a, 8, and 11 were isolated from clinical specimens and serotyped by serum neutralization and immune electron microscopy. Five of the seven types were identified consistently and identically by the two methods. Types 7a and 11 were indistinguishable by immune electron microscopy.